INDONESIA TO ENGLISH DICTIONARY AND ENGLISH TO INDONESIA BASED VISUAL BASIC 6.0 - Rian Renjana Saputra; Susi Wagiyati, SKom, MMSI (Jurnal Sistem Informasi, 2002)
In the free competition in this era, the English language is necessary, because English is the international language. And contrary to measuring technological developments in the international language and is very useful at all w hen we know more vocabulary words in the English language.Â